Combined Anterolateral Thigh and Anteromedial Thigh Flap for Extensive Extremity Reconstruction: Vascular Anatomy and Clinical Application - Jia, Ya-Chao; Chen, Hong-Hao; Kang, Qing-Lin; Chai, Yi-Min (Journal of Reconstructive Microsurgery, 2015)
Background The combined anterolateral thigh (ALT) and anteromedial thigh (AMT) flap has been previously reported for use in complicated head and neck reconstruction. However, it has not gained popularity due to the vascular variation. Here, we explore the vascular basis of this combined flap, and report its application in extremity reconstruction.Methods This study was divided into two parts: vascular anatomy and clinical application. In the anatomical study, 52 sides of adult thighs were dissected to identity vascular perforators supplying the combined ALT and AMT flap, with focus on sizeable perforators (larger than 0.5 mm) arising from the descending branch of the lateral circumflex femoral artery.Clinically, five male patients were treated by combined ALT and AMT flaps for extensive extremity reconstruction from January 2006 to December 2010. The mean age was 32 years (range, 23–45 years). The combined flap was used for covering large soft-tissue defects in forearm (n = 3) and calf (n = 2). For each patient, esthetic and functional results were recorded.Results The anatomical study showed that sizeable perforators supplying the ALT flap were present in 50 thighs (96.2%), and the perforators supplying the AMT flap were present in 32 thighs (61.5%). The combined ALT and AMT flaps were available in 30 thighs (57.7%).All five combined flaps survived completely. Skin grafts covering the donor sites healed uneventful. The mean follow-up was 9.6 months (range, 6–12 months). No complications were recorded during the follow-up.Conclusion The combined ALT and AMT flap may be used for extensive extremity reconstruction in selected patients for its great maneuverability and acceptable donor-site morbidity.
Keywords: combined flap; anterolateral thigh flap; anteromedial thigh flap; extremity reconstruction